2017
DOI: 10.1080/13880209.2017.1377736
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of green and black tea extracts on lowering serum uric acid in hyperuricemic mice

Abstract: Context: Tea (Camellia sinensis (L.) Kuntze [Theaceae]) is used to induce urination and inducing nervous excitation. Green and black teas have multifarious physiological functions. The different effects of green and black tea aqueous extracts (GTEs and BTEs) on hyperuricemia are not definitely reported. Objective: The different effects of GTEs and BTEs on lowering serum uric acid (UA) in hyperuricemic mice were determined. Materials and methods: Kunming mice were divided into nine groups (n = 6/each group). GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…The content of TRs was determined by spectrophotometer ( Roberts and Smith, 1963 ; Owuor and Obanda, 1995 ), caffeine and three kinds of TFs (TF, TF-3′, and TF-3,3′) were determined by high performance liquid chromatograph (HPLC) ( Wang et al, 2004 ; Zhu et al, 2017 ) ( Supplementary Figures 1 , 2 ). The results showed that TRs, caffeine, and title three kinds of TFs, account for 6.72%, 39.6%, 0.07%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of TRs was determined by spectrophotometer ( Roberts and Smith, 1963 ; Owuor and Obanda, 1995 ), caffeine and three kinds of TFs (TF, TF-3′, and TF-3,3′) were determined by high performance liquid chromatograph (HPLC) ( Wang et al, 2004 ; Zhu et al, 2017 ) ( Supplementary Figures 1 , 2 ). The results showed that TRs, caffeine, and title three kinds of TFs, account for 6.72%, 39.6%, 0.07%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The animals in the XLGB group were intragastrically administered XLGB (240 mg/kg body weight), BTE group were intragastrically administered BTE (100 mg/kg body weight), while those in the low- and high-dose TRs groups were intragastrically administered TRs at dosages of 9.6 mg/kg body weight and 19.2 mg/kg body weight, respectively. The BTE and TRs dose was selected based on the LD50 of rats (1860 mg/kg and 1200 mg/kg, respectively) and pharmacologic dose ( Mehri et al, 2008 ; Zhu et al, 2017 ). The model group and the sham operation group were intragastrically administered equal volumes (0.15 mL/10 g body weight) of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were divided into the following 5 groups by random: Recombinant uricase-expressing genetically engineered E. coli bacteria group (E36eu); empty vector-expressing engineered E. coli bacteria group (E36e); E. coli group (E); carboxymethylcellulose suspension group (NS); and blank control (con) group. The con group was fed with water, the rats in the other groups were fed with 5% fructose and injected intraperitoneally with oteracil potassium (100 mg/kg/day) twice daily for 8 weeks to maintain a high uric acid state, as described previously (37)(38)(39)(40)(41)(42)(43). during the entire experiment, all rats were fed standard rat chow and were given ad libitum access to water.…”
Section: Application Of Engineered Bacteria In a Rat Model Establishmmentioning
confidence: 99%
“…Excess hypoxanthine and IMP in the liver can be converted into urate through a process catalyzed by XO ( Camici et al, 2018 ). Zhu et al (2017) showed that extracts from green tea and black tea were able to inhibit ADA activity, thereby reducing serum urate levels. Furthermore, PNP catalyzes the conversion of inosine into hypoxanthine.…”
Section: Discussionmentioning
confidence: 99%